Azolium-Linked Cyclophanes: Effects of Structure, Solvent, and Counteranions on Solution Conformation Behavior - Baker, M.; Brown, David; Heath, C.; Skelton, B.; White, A.; Williams, C. (American Chemical Society, 2008)
This paper describes the synthesis, structural characterization, and solution behavior of some xylyllinked imidazolium and benzimidazolium cyclophanes decorated with alkyl or alkoxy groups. The addition of alkyl/alkoxy chains to the cyclophanes allows for studies in chlorinated solvents, whereas previous solution studies of azolium cyclophanes have generally required highly polar solvents. The azolium cyclophanes may exist in a syn/syn conformation (azolium rings mutually syn, arene rings mutually syn) or a syn/anti conformation (azolium rings mutually syn, arene rings mutually anti). The preferred conformation is significantly affected by (i) binding of bromide (ion pairing) to the protons on theimidazolium or benzimidazolium rings, which occurs in solutions of bromide salts of the cyclophanes inchlorinated solvents, and (ii) the addition of alkoxy groups to the benzimidazolium cyclophanes. Thesestructural modifications have also led to cyclophanes that adopt conformations not previously identifiedfor similar azolium cyclophane analogues.Detailed 1H NMR studies for one cyclophane identified binding of bromide at two independent sites within the cyclophane.